Identification of Ornamental Plants the Araceae and Asteraceae Families at Griya Tambakrejo Jombang for E-Catalog - Asna Lutfiatul Ummah; Anggun Wulandari; Ospa Pea Yuanita Meishanti (Jurnal Biologi Tropis, 2026)
Ornamental plants play an important role in improving the aesthetic, ecological, and educational quality of residential environments. This study aims to identify ornamental plant species from the Araceae and Asteraceae families in the Griya Tambakrejo Asri Jombang Housing Complex, describe their morphological characteristics, and compile a digital e-catalog as an information medium. The study used a qualitative descriptive approach through field observation, inventory, morphological identification, documentation, and literature study. Species identification was carried out based on diagnostic morphological characters and verified using taxonomic literature, determination keys, and botanical databases Plants of the World Online (POWO), GBIF, and Flora of Java. The results showed that there were 18 ornamental plant species, consisting of 15 species from the Araceae family and 3 species from the Asteraceae family. The Araceae family is dominated by decorative leafy plants with spadix-covered spathe-like flowers, while the Asteraceae family is characterized by capitulum-like compound flowers with diverse color variations. The presence of these two families provides aesthetic benefits by improving landscape quality, ecological benefits as air pollutant absorbers and food sources for pollinators, and educational benefits as learning objects for plant morphology and taxonomy. The inventory results were then compiled into an Instagram-based digital e-catalog containing the scientific name, common name, classification, morphological characteristics, benefits, and photo documentation of each species. This e-catalog is expected to be an information medium that is easily accessible to the public, although its effectiveness as a learning medium still requires expert validation and user testing in further research.